Analysis of Clean Water Infrastructure Development Towards Fulfillment of the Needs of The Dumai City Community - Topo Yudhoyono H; Lubna Salsabila; Karol teovani Lodan; Timbul Dompak (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2024)
This study aims to examine the development of clean water infrastructure in Dumai City to fulfill the community's clean water requirements. The clean water infrastructure possessed by the City of Dumai has failed to satisfy the comprehensive needs of the population. Consequently, the government addresses this issue by developing air infrastructure and implementing additional measures to resolve it. This scientific endeavor employs a descriptive qualitative method and the researcher’s observation. The study's findings reveal that PDAM Tirta Dumai Bersemai in Dumai City has failed to satisfy the water requirements of its residents. Consequently, development is requisite via multiple initiatives, including the establishment of a Drinking Water Supply System (SPAM) through Public Private Partnership (PPP), the National Urban Water Supply Project (NUSWP), and Regional SPAM Development via DUROLIS Regional SPAM (Dumai - Rokan Hilir – Bengkalis).